Direct and indirect costs and resource use in dementia care: A cross-sectional study in patients living at home. (March 2016) - Farré, Marta; Haro, Josep Maria; Kostov, Belchin; Alvira, Carme; Risco, Ester; Miguel, Susana; Cabrera, Ester; Zabalegui, Adelaida
Abstract: Background: Due to the high prevalence of dementia, health care needs are increasing beyond existing formal resources. In Spain, it is the family that takes care of this disease. Aims: To analyze the direct (health and non-health) and indirect economic costs related to care of people with dementia living with their informal caregiver in the home care/community environment, from the perspective of illness severity, associated comorbidity and social impact. Design: Multicentric, descriptive study. Setting: Three primary care public health centers associated with Hospital Clínic, Barcelona (Spain). Participants: Patients over 65 years old with a diagnosis of dementia, and included in a home care program. Inclusion criteria: People with a diagnosis of dementia made by a specialist neurologist; aged 65 years or older; a score ≤24 on the Mini-Mental State Examination, and identification of an informal caregiver. Exclusion criteria: Patients unable to identify an informal caregiver, and those with primary psychiatric pathology or Korsakoff's syndrome. Measurements: Use of Resources in Dementia to assess costs; Mini-Mental State Examination to evaluate cognitive capacity; Katz-Index to measure functional capacity; Neuropsychiatric Index for neuropsychiatric symptoms, and the Charlson-Index for comorbidity. Data collection took place between November, 2010 and April, 2012. Results: The average estimated monthly care costs for people with dementia in the home setting are 1956.2€ (SD 1463.9). Informal care was the major contributor to this with a mean estimated cost of 1214.86 (SD 902.68)€/month. Greater illness severity, dependency in activities of daily living, comorbidity and behavioral disturbance are associated with higher costs. Behavioral disturbance appeared as the only factor independently associated with cost in dementia care. The group of people with dementia with severe behavioral disturbance requires the most care resources with an average cost of 2545.2 (SD 1753.2)€/month. Conclusions: There is a direct association between dementia severity and increased costs. In addition, informal caregivers looking after people with dementia in Spain represent an important social cost. The independent factor associated with an increase in the total costs of patient care was neuropsychiatric symptoms.